PENGARUH PEMBERIAN KOMPOS DAN ARANG AKTIF DARI HASIL PENGOLAHAN SAMPAH PASAR TERHADAP PERTUMBUHAN DAN PRODUKSI CABAI MERAH (Capsicum annuum Linn.) - Eka Pratama; Murniati Murniati; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research to determine the interaction of compost market waste and activated charcoal  to find the best results on the growth and yield of red pepper (Capsicum annuum Linn.). This study was conducted for six months (March-August, 2016), the Experimental Station, Faculty of Agriculture, University of Riau Pekanbaru, using a randomizedblock design (RBD) factorial, consists of two factors and three replications. The first factor is the dose of compost market waste consist of 3 levels (K0=0 ton/ha, K1=6 ton/ha, K2= 12 ton/ha). The second factor is the dose of activated charcoal consist of 3 level (A0= 0 kg/ha, A1= 40 kg/ha, A2= 80 kg/ha). The results were analyzed by analysis of variance and Duncan's New Multiple Range Test (DNMRT) at 5%. The study suggest that not occur interaction of compost market waste and activated charcoal, but the combination of compost market waste and activated charcoal significantly different of plant height, height dichotomous, stem diameter, days to flowering, number of fruit per plant, fruit weight per plant and fruit weight per plot red pepper plants compost market waste dose 12 ton/ha and activated charcoal dose 40 kg/ha showed the best result inrate of plant height (82,33 cm), and production per plot (831,35 g).Keywords : Chili Plant, Compost Market Waste, Activated Charcoal